Early postoperative complications following laparoscopic-assisted modified Soave procedure for Hirschsprung’s disease: Incidence, Clavien-Dindo classification, and risk factor analysis - Xianhui Shang; Renbiao Huang; Yuanmei Liu; Hao Fu; Luping Xiang; Shiyu Xu; Yan Qu (PLoS ONE, 2025)
Objective To investigate the incidence and severity of early postoperative complications (within 30 days post-surgery) following laparoscopic-assisted modified Soave procedure for Hirschsprung’s disease (HSCR), and to analyze the factors influencing these complications. Methods A retrospective analysis was performed on the clinical data of patients who underwent laparoscopic-assisted modified Soave procedure for HSCR from January 2010 to December 2020 at our institution. Data including gender, age at surgery, clinical type, occurrence of Hirschsprung-associated enterocolitis (HAEC), presence of stoma, anemia, hypoalbuminemia, and surgery duration were collected. Patients were categorized into complication and non-complication groups based on the occurrence of early postoperative complications. The Clavien-Dindo (CD) classification system was used to grade the severity of postoperative complications, and univariate analysis was performed to identify potential factors influencing complications. Statistically significant variables were further analyzed by multivariate logistic regression. Results A total of 112 patients were included in the study, comprising 83 males (74.1%) and 29 females (25.9%). Nineteen patients (17.0%) experienced complications, including three with two types of complications. The non-complication group included 93 patients (83.0%). The complications included perianal skin erosion (2 cases, 9.1%), abdominal wound infection (1 case, 4.6%), abdominal cavity infection (1 case, 4.6%), HAEC (10 cases, 45.5%), HAEC with intestinal perforation (2 cases, 9.1%), umbilical wound dehiscence with omental exposure (1 case, 4.6%), adhesive bowel obstruction (3 cases, 13.6%), rectal retraction (1 case, 4.5%), and acute respiratory failure with laryngeal edema (1 case, 4.6%). The CD classification for postoperative complications was as follows: Grade I (3 cases, 13.6%), Grade II (11 cases, 50.0%), Grade IIIb (7 cases, 31.8%), and Grade IVa (1 case, 4.6%). Univariate analysis indicated that preoperative stoma (P = 0.029), preoperative anemia (P = 0.025), and hypoalbuminemia (P < 0.001) were significant factors influencing early postoperative complications. Multivariate logistic regression revealed that preoperative stoma (OR=4.826, 95% CI = 1.187–20.162, P = 0.028) and hypoalbuminemia (OR=9.14, 95% CI = 2.678–30.972, P < 0.001) were independent risk factors for postoperative complications. Conclusion Early postoperative complications following laparoscopic-assisted modified Soave procedure are not uncommon, with approximately one-third of cases requiring surgical reintervention. The most frequent complication was Hirschsprung-associated enterocolitis (HAEC), and most were classified as Clavien-Dindo grade II. Preoperative hypoalbuminemia and stoma creation were identified as independent risk factors, suggesting that perioperative nutritional intervention and risk stratification may help reduce the incidence of complications.